2009
DOI: 10.1080/09669580902928468
|View full text |Cite
|
Sign up to set email alerts
|

Managerial attitudes towards environmental management among small and medium hotels in Kuala Lumpur

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 9 publications
4
148
1
5
Order By: Relevance
“…Tsai et al (2012) noted this lack awareness when interviewing hotel employees in Hong Kong hotels. Kasim (2009) similarly observed this lack of awareness, particularly in small and medium sized hotels in Malaysia. This lack of awareness and understanding can often hinder any CSR initiation and implementation (Scanlon, 2007).…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Tsai et al (2012) noted this lack awareness when interviewing hotel employees in Hong Kong hotels. Kasim (2009) similarly observed this lack of awareness, particularly in small and medium sized hotels in Malaysia. This lack of awareness and understanding can often hinder any CSR initiation and implementation (Scanlon, 2007).…”
Section: Discussionmentioning
confidence: 77%
“…Finally, various studies on companies listed on the New York stock exchange indicates that the financial performance of companies that practice corporate social responsibility and sustainability often surpasses that of companies that don't (Kasim, 2009). Just as important, these companies are also strongly supported by investors in the financial markets.…”
Section: Conclusion and Limitations Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that hoteliers are mainly focusing on sustainable practices for water, electricity, and recyclable solid waste, such as bottles, can, paper, and plastics (Kasim, 2009;Kasimu, Zaiton, & Hassan, 2012;Molina et al, 2009;Pirani & Arafat, 2015). Meanwhile, documentation on hoteliers' practices towards sustainable food waste management have not been specifically given great attention by previous researchers and hence, the need for this study, particularly for Langkawi Island.…”
Section: Introductionmentioning
confidence: 92%